2011
DOI: 10.1007/s10842-011-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

A Welfare Evaluation of History-Based Price Discrimination

Abstract: We design an asymmetric duopoly model with inherited market dominance such that the dominant firm and the small firm can price discriminate based on consumers' purchase history. We show that uniform pricing softens competition leading to higher industry profits than under history-based pricing. Consumers benefit from history-based price discrimination unless the switching cost is sufficiently high and the inherited degree of dominance is sufficiently weak. A ban on history-based pricing would typically introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 21 publications
3
40
1
Order By: Relevance
“…Such history-based price discrimination (Gehrig et al, 2012) is often used as a pricing strategy in subscription markets from software 1 to communications. For example, Italian mobile incumbent TIM offers one month free and extra 4G to switching consumers, while competitors Tre and WIND reward $ E-Mail address: hinnerk.gnutzmann@unicatt.it.…”
Section: Introductionmentioning
confidence: 99%
“…Such history-based price discrimination (Gehrig et al, 2012) is often used as a pricing strategy in subscription markets from software 1 to communications. For example, Italian mobile incumbent TIM offers one month free and extra 4G to switching consumers, while competitors Tre and WIND reward $ E-Mail address: hinnerk.gnutzmann@unicatt.it.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is straightforward to see how, in a static setting, both firms would always want to have a 'poaching' offer. In this respect, it is also worth noting that this is in contrast to traditional spatial models where the location identifies brand preferences, so that for very asymmetric inherited market shares the larger firm may not offer a poaching offer given that it would be too costly to attract marginal customers that are close to the previous cut-off point, but very far from the opposite extreme where the dominant firm is located (see Gehrig et al, 2012, Section 3).…”
Section: History-based Price Discriminationmentioning
confidence: 99%
“…Over time this pricing pattern should tend to reduce market share asymmetries as larger firms are less keen on acquiring new unattached customers (Beggs and Klemperer, 1992) or poaching rivals' customers (Rhodes, 2014;Somaini and Einav, 2013). Gehrig et al (2012) found that even when firms can price discriminate between new and current customers, poaching might not take place if switching costs are sufficiently high. Moreover, where market shares are particularly skewed, the erosion of the larger firm's customer base is larger than under uniform pricing.…”
Section: Introductionmentioning
confidence: 99%
“…Gehrig et al. (, ) illustrate that when both firms have different market shares but both of them know the consumers’ purchase histories, BBPD makes the competition fiercer and decreases the profits…”
Section: Introductionmentioning
confidence: 99%
“…Individual consumer surplus is also maximal at an intermediate level of information accuracy. The impact that information has on the consumer surplus has received great attention by scholars (see, e.g., Thisse and Vives, ; Liu and Serfes, ; Esteves, ; Gehrig et al., ; Bouckaert et al., ). Our analysis suggests that a public policy aiming to maximize the consumer surplus should avoid the extreme situations where information accuracy is maximal (perfect BBPD) or minimal (uniform pricing).…”
Section: Introductionmentioning
confidence: 99%